Unexplained recurrent hematuria and clot retention following transurethral resection of the prostate (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Severe hemorrhage following a prostatectomy is a rare and serious complication. A 60-year-old male with recurrent hematuria and clot retention following transurethral resection of the prostate  (TURP) which led to anemia presented at our department and was treated with repeated clot evacuation and fulguration and lastly re-resection and fulguration succeed to stop bleeding. At 18 months follow-up, the patient had recovered well. We concluded that re-resection and fulguration on fresh tissue without opening the venous sinusoids should be considered as one of the effective treatment of choice in recurrent hemorrhage following TURP.